Forhandling om natur – kultur. En økokritisk lesning av Jörg Müller og Jörg Steiners bildebok Kaninliv (1978). (1st January 2016) - Birkeland, Tone
Abstract : Animals and wildlife have a central place in the representations of nature in children's literature, and is often presented as an unproblematic idyll. This arises from the conception of the tight relationship between children, animals and nature. The picturebook Kaninliv (1978) [ Die Kanincheninsel, 1977] by Jörg Müller and Jörg Steiner is sticking out with heavier and more disturbing themes, examining industrial society's exploitation of animals and nature, and conveys a critical eye on a fur farming involving restrictions on unfolding opportunities for the animals. The scope of this article is to discuss how the concept of nature is expressed and negotiated in the dialogue between pictures and verbal text represented in Kaninliv . Nature and wildlife will be read from an ecocritical perspective, in relation to the nature/culture dichotomy, as well as from an allegoric point of view. The analysis is a part of the research project Nature in Children's Literature : Fostering ecocitizens, initiated at Bergen University College, and is discussed in relation to a matrix developed by the research group that places the texts along the two axes "nature celebrating versus nature problematizing" and "anthropocentric versus biocentric".